Emulsification of acidic heavy oil for viscosity reduction and enhanced oil recovery. Issue 1 (2nd January 2020) - Pu, Wanfen; Shen, Chao; Tang, Xingjian; Pang, Shishi; Sun, Ding; Mei, Zilai
Abstract: Heavy oil used in this study was typical acidic heavy oil (high content of petroleum acid) and very prone to generate viscosified W/O emulsions by mixing with formation water. In order to prevent W/O emulsion formation and simultaneously reduce oil viscosity, oil-in-water emulsification was proposed and eventually sodium dodecyl sulfonate (SDS) was selected as the emulsifier due to the excellent viscosity reduction effects. The results showed that SDS could decrease oil-water interfacial tension to a certain extent and change rock wettability from oil-wet to water-wet. In addition, it was found that water content played an important role in the type of generated emulsions and viscosity-enhancing W/O emulsions were still produced at lower water content (20 ∼ 30%) even though SDS was added. The displacement experiment proved that injecting SDS solution could effectively enhance oil recover factor of the acidic heavy oil reservoir, compared with water injection. Graphical Abstract: uf0001